Availability of Loading and Unloading Equipment, Berthing Docks, Loading and Unloading Speed on Improving Port Operational Performance Through Service Digitalization - Toni, Purnama Rotua Julius; Saputra, Datep Purwa; Soekirmaan, Atong (Dinasti International Journal of Digital Business Management, 2024)
This study aims to analyze the effect of the availability of loading and unloading equipment, ship berthing docks, and loading and unloading speed on operational performance at Marunda Port, Jakarta, mediated by service digitalization. The background of this research is based on the importance of port operational efficiency in supporting economic growth, primarily through increasing loading and unloading productivity and utilizing digital technology. The research method used is a quantitative method with a linear regression approach. Data was collected by distributing questionnaires to 170 respondents who are users of Marunda Port services. The results showed that the availability of loading and unloading equipment, ship berthing docks, and loading and unloading speed significantly affected port operational performance. In addition, service digitization is proven to mediate the influence of these factors on improving operational performance. This study concludes that increasing the availability of equipment and operational efficiency of the dock and loading and unloading speed, supported by service digitalization, significantly improves the operational performance of Marunda Port, Jakarta. Implementing service digitalization is vital in improving port efficiency and competitiveness in the industrial era 4.0.